Shocks or photoionization: direct temperature measurements of the low-ionization gas in quiescent galaxies. Issue 1 (8th August 2018) - Yan, Renbin
ABSTRACT: The ionization mechanism of the low-ionization gas in quiescent red-sequence galaxies has been a long-standing puzzle. Direct temperature measurements would put strong constraints on this issue. We carefully selected a sample of quiescent red-sequence galaxies from Sloan Digital Sky Survey. We bin them into three bins with different [N ii ]/H α and [N ii ]/[O ii ] ratios, and we measure the temperature-sensitive [O iii ] λ4363, [N ii ] λ5755, [S ii ] λλ4068, 4076, and [O ii ] λλ7320, 7330 lines in the stacked spectra. The [S ii ] doublet ratios indicate the line-emitting gas is in the low-density regime (∼10–200 cm −3 ). We found the temperatures in the S + zones to be around 8000 K, the temperatures in the O + zone to be around 1.1–1.5 × 10 4  K, and the temperatures in the N + zones to be around 1–1.4× 10 4  K. The [O iii ] λ4363 line is not robustly detected. We found that the extinction corrections derived from Balmer decrements would yield unphysical relationships between the temperatures of the S + zones and O + zones, indicating that the extinction is significantly overestimated by the measured Balmer decrements. We compared these line ratios with model predictions for three ionization mechanisms: photoionization by hot evolved stars, shocks, and turbulent mixing layers. For the photoionization and shock models, the hot temperatures inferred from [S ii ] and [N ii ] coronal-to-strong line ratios require metallicities to be significantly subsolar. However, the [N ii ]/[O ii ] line ratios require them to be supersolar. None of the models could simultaneously explain all of the observed line ratios, neither could their combinations do.